2022
DOI: 10.7554/elife.71348
|View full text |Cite
|
Sign up to set email alerts
|

Gene age shapes the transcriptional landscape of sexual morphogenesis in mushroom-forming fungi (Agaricomycetes)

Abstract: Multicellularity has been one of the most important innovations in the history of life. The role of gene regulatory changes in driving transitions to multicellularity is being increasingly recognized; however, factors influencing gene expression patterns are poorly known in many clades. Here we compared the developmental transcriptomes of complex multicellular fruiting bodies of eight Agaricomycetes and Cryptococcus neoformans, a closely related human pathogen with a simple morphology. In-depth analysis in Ple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 128 publications
(240 reference statements)
6
45
0
1
Order By: Relevance
“…All-vs-all similarity searches of the 123 proteomes were performed with MMseqs2 51 using three iterations, with sensitivity set to 6.5, max-seqs to 15,000, e-profile set to 0.001, a preliminary coverage threshold set to 0.2, and an e-value threshold set to 1e -4 . We then performed an asymmetric coverage filtering (requiring 20% coverage for the longer and 80% for the shorter protein) and Markov clustering with an inflation parameter 2.0 52 as described previously 53 . After clustering, we removed contaminating proteins from gene families following the logic of Richter et al 47 .…”
Section: Methodsmentioning
confidence: 99%
“…All-vs-all similarity searches of the 123 proteomes were performed with MMseqs2 51 using three iterations, with sensitivity set to 6.5, max-seqs to 15,000, e-profile set to 0.001, a preliminary coverage threshold set to 0.2, and an e-value threshold set to 1e -4 . We then performed an asymmetric coverage filtering (requiring 20% coverage for the longer and 80% for the shorter protein) and Markov clustering with an inflation parameter 2.0 52 as described previously 53 . After clustering, we removed contaminating proteins from gene families following the logic of Richter et al 47 .…”
Section: Methodsmentioning
confidence: 99%
“…Hypothetical genes are often fungal or lineage specific, and thus have often been less well characterized than deeply conserved genes at higher taxonomic levels. Although greater degrees of transcriptional divergence of hypothetical genes may be attributable to neutrally arising expression variation widely observed in young genes because of weaker evolutionary constraint ( 56 ), our systemic knockout studies for hypothetical genes demonstrated that these hypothetical genes have evolved to be necessary for successful sexual development, showing significant shifts in their expression levels in certain groups of fungi.…”
Section: Discussionmentioning
confidence: 83%
“…It was shown that deeply conserved genes (“old genes”), as well as newly emerged genes (“young genes”) tend to be expressed during specific developmental stages in fungi, playing important roles in sculpting fruiting body morphologies ( 56 ). To assess the ages of the annotated genes in the F. graminearum and N. crassa genomes, we sorted hypothetical genes and genes with predicted functional domains (henceforth referred as “functional genes”) using a phylostratigraphic approach, in which ages of the phylogenetically classified genes were assigned based on the set of species that share orthologous genes.…”
Section: Resultsmentioning
confidence: 99%
“…Many comparative studies have been conducted to clarify the driven factors in fungal morphogenesis and multicellularity construction (Kiss et al 2019; Krizsán et al 2019; Varga et al 2019; Merényi et al 2020; Miyauchi et al 2020; Virágh et al 2022). Questions have been raised on the robustness of the hourglass model in fruiting body development in some fungal clades (Merényi et al 2022).…”
mentioning
confidence: 99%
“…Questions have been raised on the robustness of the hourglass model in fruiting body development in some fungal clades (Merényi et al 2022).…”
mentioning
confidence: 99%